A comparative study of a new challenge-based learning model for engineering majors - Robledo-Rella, V.; Neri, L.; García-Castelán, R. M. G.; Gonzalez-Nucamendi, A.; Valverde-Rebaza, J.; Noguez, J. (Frontiers in Education, 2025)
Current society needs professionals able to identify and collaboratively solve the main challenges of the 21st century. Students must be trained to face real challenges in their future workplaces and to acquire the necessary competencies to succeed in the current-day global world. As an answer to such needs, the Tecnologico de Monterrey launched in 2019 its competency-based Tec21 educational model, emphasizing the development of disciplinary and transversal competencies using a challenge-based learning (CBL) model. The present contribution is aimed at measuring the effectiveness of this model compared to the more traditional previous learning (PL) model. We present a quasi-experimental study comparing the academic performance of 1705 freshman engineering students, 43% enrolled in the PL model and 57% enrolled in the CBL model. Although the CBL model was applied to all the institution’s majors, the paper is focused on the freshman physics courses of the engineering majors. The study spans seven semesters, from Spring 2018 to Spring 2021. It was found that the overall student performance, measured by the average final course grades, improved by 9.4% in the CBL model compared to the PL model. On the other hand, the challenge average grades of the CBL model were like the project average grades of the PL model. Additionally, two-year opinion surveys about the CBL model were administered to 570 students. It was found that 71% of the students expressed a favorable perception of the CBL model in terms of their competencies development and their ability to solve problems. It is suggested that the explicit integration of physics, math, and computing concepts through the solution of real-life challenges in the CBL model bears a stronger student engagement and thus yields better general learning outcomes than the PL model.